2005
DOI: 10.1016/j.femsec.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of warming and fertilization on nitrogen-fixing microbial communities in the Canadian High Arctic

Abstract: The impacts of simulated climate change (warming and fertilization treatments) on diazotroph community structure and activity were investigated at Alexandra Fiord, Ellesmere Island, Canada. Open Top Chambers, which increased growing season temperatures by 1-3 degrees C, were randomly placed in a dwarf-shrub and cushion-plant dominated mesic tundra site in 1995. In 2000 and 2001 20N:20P2O5:20K2O fertilizer was applied at a rate of 5 gm(-2) year(-1). Estimates of nitrogen fixation rates were made in the field by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 33 publications
5
67
1
Order By: Relevance
“…Long-term disturbance of forest soils due to clearcutting led to distinctly different nifH communities with new dominant TRFs and losses of previously dominant genotypes and additionally, these communities exhibited atypical seasonal variation (Shaffer et al, 2000). Deslippe et al (2005) also noted that nifH communities were strongly structured by OTC warming, with NMS ordinations showing differences between control plots and OTCs at lowland sites that developed over the growing season. Sequences obtained from GenBank.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Long-term disturbance of forest soils due to clearcutting led to distinctly different nifH communities with new dominant TRFs and losses of previously dominant genotypes and additionally, these communities exhibited atypical seasonal variation (Shaffer et al, 2000). Deslippe et al (2005) also noted that nifH communities were strongly structured by OTC warming, with NMS ordinations showing differences between control plots and OTCs at lowland sites that developed over the growing season. Sequences obtained from GenBank.…”
Section: Discussionmentioning
confidence: 91%
“…However, the link between shifts in microbial community structure (measured by changes in gene frequency, abundance and richness) and corresponding changes in the processes mediated by these communities has not been satisfactorily demonstrated. Deslippe et al (2005) found little relationship between nifH genotype diversity and nitrogen-fixation rates. In addition, although excess nitrogen should negatively affect nitrogen fixation (Zehr et al, 2003), the diversity of the nitrogen-fixing community assessed using the functional gene nifH has not been shown to diminish in such cases (Piceno and Lovell, 2000).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations